Environment that causes diseases: article review - Adilla Dwi Nur Yadika (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Environmentally induced diseases have become a global concern due to their significant impact on public health. The environment plays a significant role in increasing or decreasing the risk of disease through various factors, such as air, water, and soil pollution and exposure to hazardous chemicals. This review aims to analyze the literature on environmental factors that trigger diseases, including infectious diseases, chronic diseases, and mental health disorders, and to understand the mechanisms and impacts caused. Research Methodology: This study used a systematic literature review of scientific articles, research reports, and other reliable sources published in the last two decades. Data were collected, analyzed, and grouped based on the type of environmental factors and their association with various diseases. Result: Studies have shown that air pollution is a major cause of chronic respiratory diseases, such as asthma and chronic obstructive pulmonary disease (COPD), while water pollution and poor sanitation trigger outbreaks of infectious diseases such as diarrhea and cholera. Exposure to hazardous chemicals, such as pesticides and heavy metals, also contributes to increased risks of cancer and neurological disorders. In addition, environmental degradation, such as deforestation and climate change, exacerbate the spread of vector-borne diseases, such as malaria and dengue fever. Conclusion: An unhealthy environment is key in triggering various diseases that endanger public health. Mitigation efforts, such as reducing pollution, improving water quality, and protecting ecosystems, are essential to minimize adverse health impacts. The study recommends increasing cross-sector collaboration and strengthening environmental policies to create an environment that supports public health.